2 Exploratory analysis of postprogression and patient-centered outcomes in ariel3: a phase 3, randomized, placebo-controlled study of rucaparib maintenance treatment in patients with recurrent ovarian carcinoma. (18th September 2019) - Coleman, R; Oza, AM; Lorusso, D; Aghajanian, C; Oaknin, A; Dean, A; Colombo, N; Weberpals, JI; Clamp, AR; Scambia, G; Leary, A; Holloway, RW; et al.
Abstract : Objectives: In ARIEL3, rucaparib maintenance treatment significantly improved progression-free survival (PFS) vs placebo. A prespecified exploratory analysis investigated postprogression outcomes. Additionally, a post hoc exploratory analysis investigated patient-centered outcomes during rucaparib maintenance treatment. Methods: Patients were randomized 2:1 to receive oral rucaparib (600 mg BID) or placebo. Postprogression endpoints included time to start of first subsequent therapy (TFST), time to second investigator-assessed PFS or death (PFS2), and time to start of second subsequent therapy (TSST); overall survival data are not yet mature. Patient-centered outcomes included quality-adjusted investigator-assessed PFS (QA-PFS) and quality-adjusted progression-free time without symptoms or toxicity (Q-TWiST). Analyses are presented for the predefined BRCA -mutant cohort and the intent-to-treat (ITT) population. Results: The visit cutoff dates for efficacy and safety were April 15, 2017, and December 31, 2017, respectively. Postprogression and patient-centered outcome data are given in the table 1 . The most common treatment-emergent adverse events (TEAEs) of any grade (rucaparib vs placebo) were nausea (75.8% vs 36.5%), asthenia/fatigue (70.7% vs 44.4%), dysgeusia (39.8% vs 6.9%), and anemia/decreased hemoglobin (39.0% vs 5.3%). Any grade TEAEs of nausea, asthenia/fatigue, and anemia/decreased hemoglobin led to discontinuation in only 2.7%, 1.6%, and 2.7% of rucaparib-treated patients. Conclusions: Rucaparib significantly improved clinically meaningful postprogression outcomes vs placebo in the BRCA -mutant cohort and ITT population. The quality-adjusted analyses, which incorporated patient-centered perspectives during rucaparib maintenance treatment, confirmed the benefit of rucaparib vs placebo. The updated safety profile of rucaparib in ARIEL3 was consistent with prior reports.